Dampak Program Perbaikan Kualitas Jalan Kabupaten Eks-Jalan Desa Terhadap Kesejahteraan Masyarakat di Kabupaten Banyumas - Raharjo, Kabul (Public Administration, Faculty of Politics and Social Science, Universitas Jenderal Soedirman, Indonesia, 2022)
Banyumas Regent Regulation Number: 620/302/Year 2016, concerning Designation of Roads in Banyumas Regency states that several village roads have been changed to district roads. A study is needed to see how the impact of public policy in the form of changing the status of village roads to district roads. The formulation of the problem in this research is whether there is a positive and significant impact between the improvement of district roads which are ex-village roads on the welfare of the community (in terms of social benefits and social costs)?. Types of quantitative research. The research variables consisted of the independent variable (X) repairing district roads, ex-village roads, the intermediate variable (Z) economic benefits, and the dependent variable (Y) community welfare. Respondents, namely the village head or the village secretary whose area experienced a change in the status of the former village road, amounted to 137 people out of 192 assessed roads. Data collection using google form which has been tested for validity and reliability. Data analysis was univariate and bivariate. Bivariate analysis with Chi Square test and Kendal Tau correlation test. The results showed that 52.6% stated that the road conditions were bad. The condition of road infrastructure is still poor, including road surface (48.4%), road shoulder (40%), side drainage channel (58.9%), talud (50.6%), bridge/culvert surface (33 ,3%), abutments (36%) and side safety of bridges/culverts (36%). The economic benefit variable showed 54.7% stated that it was not useful, the level of welfare indicated that it was not prosperous (52.6%). The results of the bivariate analysis show that there is an effect of road infrastructure on ex-village roads on economic benefits, there is an effect of economic benefits on welfare and there is no direct effect of road infrastructure on ex-village roads on community welfare. The conclusion is that the policy in the form of changing the status of district roads to former new village roads has an impact on increasing community welfare (from the aspect of social benefits and social costs) by 53.8%. Suggestions for local governments to plan district road maintenance programs must be well and technically right on target, namely by building good road drainage in addition to road surface maintenance. Keywords: former village road, welfare, road quality